Optimum configuration design and sensitivity analysis of the 3-RRR PPMs with a general kinematic model. Issue 5 (4th May 2022) - Wang, Kun; Xie, Zhijiang; Li, Zhongyi; Bai, Shaoping
Abstract: In this work, a parameterized model of 3-R RR planar parallel manipulator is proposed, aiming to optimize the overall performance with optimum shapes and sizes of the base and mobile platforms. In the model, the inverse and direct kinematics are addressed, upon which the global kinematic performance in terms of dexterity index is calculated and analyzed. A shape and dimensional optimization is accomplished through the atlas-based method. Optimum configurations are obtained from the global performance atlases. Moreover, sensitivity analysis of overall kinematic performance with respect to each configuration parameter of planar 3-R RR parallel manipulator is performed to reveal the influences of the design parameters. A case study is included to present a more detailed design of 3-R RR manipulator.